Impact of COVID-19 pandemic in surgical training of Junior Residents in general surgery - García-Quijada García, Javier; Sanz Muñoz, Paloma; Salazar Carrasco, Andrea; Corral, Octavio Jorge; Delgado Millán, Miguel Ángel (Heliyon, 2023)
Background: The pandemic caused by SARS-CoV2 has had a huge impact on our health system. Due to both cancellation of elective surgery and restructuring in departments at most medical centers, surgical residents face a potential training deficit in their specialty. This study aims to objectively analyze and quantify the impact of the pandemic on the surgical activity of residents, in the setting of emergency and elective surgery, to assess whether this period has really supposed a training deficit. Material and methods: A descriptive analysis is proposed, comparing the number of procedures performed by residents of our department during the year prior to the pandemic and during the pandemic, clustering them into different subgroups. Results: The results give an optimistic outlook. In the first place, in elective surgery, despite the lower procedures performed in absolute numbers, the proportional participation of residents in the scheduled surgeries increased in all the subgroups analyzed, finding statistically significant differences and finally approaching the total number of procedures in both periods, without relevant differences in the comparison. As for emergency surgery, residents also increased their proportional participation in most subgroups, in this case reaching more total procedures, even in absolute numbers. Conclusion: Therefore, the results seem to indicate that the teaching effort made by staff surgeons of the department has managed to palliate, in most of the subgroups analyzed, the decrease in surgical activity that the pandemic has produced, so, at least in the area of surgical practice, the impact of the pandemic has probably been reduced comparing to previous expectations.
Keywords: pandemic; resident; SARS-CoV2; surgical training; teaching; Scopus; JCR